The Eportfolio: How can it be used in French as a second language teaching and learning? - Karsenti, Thierry; Collin, Simon (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education, 2010)
Originally used in artistic circles, the portfolio is quickly gaining ground in French as a second language teaching and learning. For example, the European Language Portfolio (ELP), under the auspices of the European Council, is a tool that is rapidly adaptable to advances in Web 2.0 technology. In this context, we draw a portrait of the portfolio in French as a second language (FSL) education and cite the advantages of the electronic portfolio. Finally, we draw on empirical results, from a specific eportfolio, eduportfolio, to illustrate its potential for FSL teaching and learning.